A novel class C beta-lactamase (FOX-2) in Escherichia coli conferring resistance to cephamycins. - Bauernfeind, A (1997)
An Escherichia coli strain resistant to a broad spectrum of beta-lactams, including cephamycins, was isolated from a patient suffering from urinary tract infection. A resistance plasmid (pMVP-7) was transferred from the clinical isolate to an Escherichia coli recipient. Both strains produce a cefoxitin-hydrolyzing beta-lactamase focusing at pI 6.7. The phenotype was similar to that of a Klebsiella pneumoniae strain producing cephamycinase FOX-1, so primers were selected from the FOX-1 sequence to amplify the bla gene of the transconjugant. The PCR product obtained was sequenced. The percentage of identity of the deduced amino acid sequence with sequences of other AmpC-type beta-lactamases was 96.9% with FOX-1, 74.9% with CMY-1, and 67.7% with MOX-1. This new plasmid-mediated enzyme is most closely related to FOX-1 (11 amino acid exchanges). We therefore propose the designation FOX-2.